Pelatihan Integrasi Nilai Budaya Lokal dalam Organisasi Santri: Upaya Meningkatkan Komitmen Berorganisasi di Rajabasa - Rusman, Tedi; Nurdin, Nurdin; Wulan, Mutiasari Nur; suroto, suroto; Wijoyo, Hadi; Turnip, Samuel; Salshabella, Dhea Clara (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This community service program aims to enhance santri’s understanding of Lampung local cultural values and strengthen their organizational commitment through a series of training and mentoring activities. The program was carried out at MWCNU Rajabasa using a participatory approach that actively engages participants throughout the learning process. The activities included cultural value dissemination, interpersonal communication training based on local wisdom, organizational roleplay simulations, and focused group discussions. The results showed a significant improvement in participants’ understanding of local cultural values, as indicated by the increase from initial to final evaluation scores. Additionally, santri demonstrated more cooperative and culturally grounded interactions, reflecting the application of piil pesenggiri, nemui nyimah, juluk adok, and sakai sambayan. This strengthened cultural awareness contributed to higher organizational commitment, seen through increased participation, responsibility, and engagement in organizational activities. This program highlights that integrating local cultural values is an effective strategy for character building and sustaining community-based santri organizations.